Indonesian Learners’ Difficulties In Understanding The Meaning Of Present Perfect Form In English - FX Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2002)
This concise essay is a summary of a limited research project attempting to investigate Indonesian learners’ problems in understanding the English perfect forms. It consists of four parts. Firstly the introduction, which gives an outline of what the essay is about. The second part, a brief literature review, discusses the basic verb phrase structure in English and Indonesian. The third part is a prediction of learners' likely difficulties, and hypotheses based on the ideas drawn from the literature review. Then, the methodology section, the fourth part, discusses how the study is conducted. The fifth part is the result and discussion of the findings, which is finally followed by the conclusion